Detection of Nematode on Feces of Snail at Malang, East Java - Niluh Selly Frantika; Kusnoto; Lucia Tri Suwanti; Imam Mustofa; Endang Suprihati; Hani Plumeriastuti (Universitas Airlangga, 2025)
Acathina fulica is a terrestrial mollusk that often invades terrestrial vegetation that has tropical and subtropical climates. Acathina fulica has been widely reported in environments as diverse as urban areas, forests, capoeiras, caatings, plantations, decomposing materials, savannahs and vegetable gardens. Soil is source of food and a defense strategy for A. fulica, therefore it has an important role for them. Therefore, A. fulica may be host several species of nematodes. Microscopic examination of snails A. fulica fecal samples in Cemorokandang Village, Malang City using the native method aimed to detect Rhabditis spp. The results showed that 14 (12.5%) out of 112 samples contained Rhabditis spp. The genus rhabditis belongs to the Rhabditidae family and is one of the free-living nematodes. This species has long been known and of concern in the veterinary world. The genus rhabditis has been reported to have infected humans and have been isolated from urine samples, vaginal swab, and human stool. The research was conducted in the dry season with low rainfall. Nematode of the genus Rhabditis spp. can be naturally found in humid places and decaying organic matter.